Assessment of timber floors by means of non-destructive testing methods. (30th December 2015) - Ilharco, Tiago; Lechner, Thomas; Nowak, Tomasz
Abstract: In the process of rehabilitation of built heritage, the preservation of timber floors is an essential issue. These structures have characteristics that are not entirely known, namely the connections between elements, the load distribution between beams, the importance of secondary elements, such as struts and floorboard, for the attenuation of vibrations and reduction of deformations of the floor, etc. If properly analysed and considered, these aspects can contribute to upcoming well-succeeded interventions, improving the global behaviour of the floors and, consequently, of the buildings. One of the focuses of the present paper is the assessment of the global behaviour of timber floors by means of dynamic analysis, which is one of the non destructive tests (NDT) used to evaluate the reference properties of the wood. In particular, this technique allows estimating the timber floors' stiffness and, consequently, assessing their efficiency and integrity. Furthermore, the paper focuses on the use of other NDT methods, namely involving stress-wave timing, X-ray and resistance drilling, which can provide very useful information about these characteristics. The information obtained with the combined NDT allows a better understanding of the timber floors behaviour and the implementation of more efficient rehabilitation and (or) strengthening techniques.